Membimbing Siswa Menjadi Wirausaha Muda Melalui Pendidikan Kewirausahaan Sekolah - idris, muhammad; Wahira; Romansyah; Hikmawati (IAI DDI POLEWALI MANDAR, 2024)
Entrepreneurship education plays a crucial role in preparing young generations to face the challenges of the workforce in the era of globalization. By combining theory and practice, this education enhances students' creativity, risk-taking, and problem-solving skills, which are essential traits of successful entrepreneurs. The project-based learning (PBL) approach has proven effective in developing entrepreneurial mindsets through hands-on experiences such as business simulations and incubator programs. However, implementing entrepreneurship education in schools faces challenges, including insufficient teacher training, limited practical facilities, and curricula that emphasize theory over practical application. To overcome these barriers, collaboration between schools, business communities, and governments is needed to create a supportive entrepreneurial ecosystem. With this approach, entrepreneurship education can serve as a strategic solution to reduce youth unemployment and foster young entrepreneurs who are innovative and competent.